PENGARUH DRESSING PASTA KALSIUM HIDROKSIDA TERHADAP JENIS DAN JUMLAH KOLONI BAKTERI AEROB PADA SALURAN AKAR GIGI DESIDUI NEKROTIK - , ANGELICA ISADORA JONATHAN (ANGIE); , DR. drg. Indah Titien, S., S.U., Sp.KGA(K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Infected pulp in deciduous tooth can cause necrotic process. Root canal dressings are required to sterilize necrotic primary teeth, one of them is calcium hydroxide. It has bactericidal effect because it releases hydroxyl ions to inhibit bacterial growth. The objective of this study was to observe the association between calcium hydroxide root canal dressing with the species and bacterial profile. Eleven necrotic teeth were observed, three teeth were excluded due to failure restoration. Examinations were taken to know the species and bacterial profile that can be found before and after dressing with calcium hydroxide. Dressings were applied for 7 days. The result shows that in 8 root canals, aerobic bacteria were found. Aerobic bacteria found before dressing were Streptococcus alpha and Klebsiella pneumoniae. Aerobic bacteria found after dressing was Streptococcus alpha. Mean of aerobic bacteria before dressing was 31608,75 CFU/ml. Mean of aerobic bacteria after dressing was 4141,25 CFU/ml. The Wilcoxon result indicated that there was significance difference of bacterial profile before and after dressing (p<0.05). It is concluded that S. alpha and Klebsiella pneumoniae were found before dressing and S. alpha were found after dressing. The bacterial profiles in deciduous root canals were decreased after root canal dressing with calcium hydroxide.